EĞİTİMDE DİJİTAL ÖYKÜ ARAŞTIRMALARININ İNCELENMESİ VE DİJİTAL ÖYKÜ ARAÇLARININ SINIFLANDIRILMASI. - ÜNAL, Cahide; ÇAKIR, Hüseyin (Turkish Journal of Social Research / Türkiye Sosyal Araştırmalar Dergisi, 2023)
As technology continues to advance, "Digital Storytelling" has emerged as a potent educational tool. A digital story can be described as the amalgamation of various multimedia tools, including text, images, audio, video, and music, aimed at conveying information on a specific topic. This study classifies digital storytelling tools by analyzing master's and doctoral dissertices, as well as articles that employ the digital storytelling method. To achieve this, we examined master's and doctoral theses, along with articles on digital stories from national and international journals, which are found in the national thesis center. These resources also provided insights into the digital storytelling software utilized. Upon examining eighty-one studies, we found that despite the wide array of digital storytelling tools available, teachers primarily opt for desktop programs. Digital storytelling appears to be utilized across all levels and disciplines of education, ranging from pre-school to university. This study also evaluated thirty-five digital storytelling tools mentioned in dissertations and articles, and those employed in education for digital storytelling purposes. While determining these software tools, the ones most frequently used in the related articles and theses were prioritized. This research aims to assist teachers in choosing appropriate digital storytelling tools by classifying them according to their usage and by identifying the features and application areas of these tools. The ability of teachers to utilize these software tools to create digital stories will hinge on their understanding of the features and intended uses of the software.